THE EFFECT OF STEM-BASED E-MODULE ON STUDENTS' CREATIVE THINKING IN OXYGEN FOR LIFE TOPIC FOR JUNIOR HIGH SCHOOL BASED ON GENDER - Ivaldy Gesca Deandra, - (2018)
The needs of developing competent human resources on 21st-Century skills nowadays are become an issue. One of the skills is creative thinking skill. In this research, STEM-based E-Module can be an option. Investigate the effect of implementing STEM-based E-Module, investigate the differences between the female and male group on their creative thinking, and determine students' impression on STEM-based E-Module are the objectives that have to be reached. The pre-experiment method with one group pre-test and post-test was conducted through a research subject of 8th-grade students at a private school in Bandung that taken from a convenient sampling. Creative thinking was determined by a test of Verbal Torrance Test of Creative Thinking (TTCT) in Oxygen for Life topic, while students' impression obtained by a questionnaire. The result of this research stated that there is a significant difference between post-test of Verbal TTCT and minimum criteria of mastery learning that has been decided as standard, which is 65. The analysis was using t-paired test using SPSS. In differentiating between female and male group on their creative thinking, independent t-test was conducted. But there is no significant differences between female group and male group on their creative thinking. ..... Pada saat ini, setiap negara harus mengembangkan sumber daya manusia yang kompeten untuk bersaing pada abad ke-21 serta memiliki keterampilan abad ini. Salah satu keterampilan tersebut adalah keterampilan berpikir kreatif. Pada penelitian ini, E-Modul dapat menjadi satu solusi dalam mempersiapkan keterampilan yang dibutuhkan, terutama keterampilan berpikir kreatif. Penelitian ini bertujuan untuk meningkatkan kemampuan berpikir kreatif siswa sebagai efek penggunaan E-Modul, menyelidiki perbedaan antara kelompok laki-laki dan perempuan pada keterampilan berpikir kreatif mereka setelah implementasi, serta meminta pesan dan kesan siswa terhadap media pembelajaran ini. Metode yang digunakan dalam penelitian ini adalah pra-eksperimen, dengan subjeknya merupakan siswa kelas 8 yang terpilih lewat convenient sampling. Keterampilan berpikir kreatif dinilai dengan menggunakan Verbal (TTCT) untuk topik Oksigen untuk Kehidupan. Hasilnya dapat diketahui jika terdapat perbedaan yang signifikan antara nilai pos-tes pada tes berpikir kreatif dan kriteria ketuntasan minimal (KKM). Namun, tidak ditemukan perbedaan signifikan antara skor post-test laki-laki dan kelompok perempuan.